2020
DOI: 10.1186/s13007-020-00632-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of novel precision viticulture tool for canopy biomass estimation and missing plant detection based on 2.5D and 3D approaches using RGB images acquired by UAV platform

Abstract: Background: The knowledge of vine vegetative status within a vineyard plays a key role in canopy management in order to achieve a correct vine balance and reach the final desired yield/quality. Detailed information about canopy architecture and missing plants distribution provides useful support for farmers/winegrowers to optimize canopy management practices and the replanting process, respectively. In the last decade, there has been a progressive diffusion of UAV (Unmanned Aerial Vehicles) technologies for Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…According to Campos et al [45], the combination of information extracted from UAV flights and a decision support system resulted in a 45% reduction of pesticide foliar application in vineyards. The 3D modelling of vineyards is also useful for the evaluation of vine-rows features (such as inter-row spacing or row orientation) [17] and for the detection of missing plants [46]. In addition, the estimation of vine dimensions throughout a season would allow the generation of dynamic growth maps, and the identification of areas were canopy management operations could be beneficial or needed to be re-designed [16].…”
Section: Discussionmentioning
confidence: 99%
“…According to Campos et al [45], the combination of information extracted from UAV flights and a decision support system resulted in a 45% reduction of pesticide foliar application in vineyards. The 3D modelling of vineyards is also useful for the evaluation of vine-rows features (such as inter-row spacing or row orientation) [17] and for the detection of missing plants [46]. In addition, the estimation of vine dimensions throughout a season would allow the generation of dynamic growth maps, and the identification of areas were canopy management operations could be beneficial or needed to be re-designed [16].…”
Section: Discussionmentioning
confidence: 99%
“…The results are improved by selecting an early period (preferably belonging to phase 2- Figure 2) to conduct grapevine detection, with grapevines with a lower leaf cover, preventing the existence of vegetation in areas with no plants [21]. In Di Gennaro and Matese [44], 3D and 2.5D methods were compared for vineyard biomass and plant detection, but individual grapevine detection was not performed. In that study, as for missing plants, an overestimation was observed in the 3D-based method, false negatives were related to the existence of new plants while some false positives were due to different grapevine canopy thickness.…”
Section: Individual Grapevine Detectionmentioning
confidence: 99%
“…Following this approach, it becomes possible to use high resolution multispectral images to individually quantify the components of the photosynthetically active biomass (PAB), obtaining the spectral response of the canopy from 2D analysis and biomass data from 3D analysis, thus overcoming the limit of the traditional NDVI index in the characterization of vigour. In support of the geometric approach is added the fact that it can be obtained with common RGB cameras, with minimum costs and very high performance derived from the extreme spatial resolution 6 . In general, the geometric approach presented in this paper can be applied on many tree crops, however on some exceptions with full soil covering such as overhead trellis system 21 and on extended crops such as horticultural crops or cereals, the NDVI index remains the only applicable solution for estimating production and vegetative parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Geometric variables related to canopy thickness and volume were calculated using the 2.5D methodology with Matlab v.2019a (Mathworks, Natick, MA, USA) described in Di Gennaro and Matese (2020) 6 . Starting from the DEM of vines enclosed within a polygon grid, canopy thickness and vine number are extrapolated through the binarized image of the canopy extracted from each polygon grid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation